Conflicting Factors in the Design of Naturally Ventilated Apartment in Warm Humid Tropics - Putri Melati Dewi; I Gusti Ngurah Antaryama (Jurnal Sains dan Seni ITS, 2017)
One of the most effective strategies in designing a passive ventilation apartment in the warm humid tropical clime is to maximize airflow in a building. However designing such kind of apartment often contradicts with socio-economic aspects such as land usage, privacy and security. The reason for that is on one hand naturally ventilated apartment means maximizing openings as much as possible, on the other hand middle-upper income class people need high security and privacy. Method used for designing this apartment is Evidence Based Design, which makes use of current best evidence from research and precedent in the topic of thermal comfort and residential buildings. This passive design apartment seeks optimum solution to overcome contradictory aspects of thermal comfort and socio-economy, by integrating the main concept of maximizing airflow and maintaining privacy through architectural elements.